2006
DOI: 10.1029/2005jf000355
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for floatation or near floatation in the mouth of Kamb Ice Stream, West Antarctica, prior to stagnation

Abstract: [1] Ice-penetrating radar profiles reveal distinctive internal structure within the flat ice terrains that bound the lower reaches of the now stagnant Kamb Ice Stream, West Antarctica; slightly warped but continuous upper layers overlie extensive deep line diffractors located at a uniform depth several hundreds of meters above the bed. On the basis of their orientation and morphology we interpret the line diffractors to be the tips of basal crevasses. At the boundary between these terrains and the inter-ice st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 64 publications
7
67
0
Order By: Relevance
“… Jezek [1984] mapped the spatial pattern of basal reflectance downstream of Crary Ice Rise and estimated grounding line retreat past the ice rise within the last 1000 years on the basis of the pattern of reflection strength within the ice shelf. Catania et al [2006] imaged downwarped internal stratigraphy in the low‐relief ice terrain on the downstream end of the ridge between KIS and WIS and interpreted them as evidence of a grounding line well inland of its present location within the last few hundred years. Together, these observations suggest 100s of km of grounding line retreat and readvance on century timescales.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… Jezek [1984] mapped the spatial pattern of basal reflectance downstream of Crary Ice Rise and estimated grounding line retreat past the ice rise within the last 1000 years on the basis of the pattern of reflection strength within the ice shelf. Catania et al [2006] imaged downwarped internal stratigraphy in the low‐relief ice terrain on the downstream end of the ridge between KIS and WIS and interpreted them as evidence of a grounding line well inland of its present location within the last few hundred years. Together, these observations suggest 100s of km of grounding line retreat and readvance on century timescales.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors suggested that the low‐relief ice plain could allow grounding line retreat rates up to 20 times faster than the observed rate, a range that embraces the rates generated in our simulations. It is possible that the upstream incursion of the KIS grounding line suggested by Catania et al [2006] is a result of WIS stagnation. Our models do not, at present, extend far enough upstream to verify this suggestion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include time-varying perturbations in local sea level (Gomez et al, 2012), accumulation, ice viscosity (Schoof, 2007), dynamism of bed friction (Sergienko and Hindmarsh, 2013) and changes in the stabilizing effect of the surrounding ice shelves (Gudmundsson, 2013;Wright et al, 2014) through basal melting induced by ocean temperature changes (Pollard and DeConto, 2009;Hellmer et al, 2012). Whether the readvance proposed in our revised model is due to external forcing (e.g., less warm water penetrating under the FRIS) or internal dynamics (e.g., GIA uplift leading to bed shallowing and grounding line readvance) is difficult to resolve by ice-sheet modelling owing to the sensitivity of grounding-line motion to melt, but either process could have operated here (Wright et al, 2014) or in other areas of the WAIS such as the Amundsen Sea embayment and the Ross Sea (Bindschadler et al, 1990;Catania et al, 2006). The possibility that some of these grounding lines might currently be advancing has implications for forecasting their response to warming associated with global change, as the initiation of unstable retreat would require changes in controls such as sub-ice shelf melt (Wright et al, 2014).…”
Section: Impact Of the Revised Holocene Ice-loading Simulation On Bedmentioning
confidence: 99%